2015
DOI: 10.1093/hmg/ddv214
|View full text |Cite
|
Sign up to set email alerts
|

Serum proteomic profiling reveals fragments of MYOM3 as potential biomarkers for monitoring the outcome of therapeutic interventions in muscular dystrophies

Abstract: Therapy-responsive biomarkers are an important and unmet need in the muscular dystrophy field where new treatments are currently in clinical trials. By using a comprehensive high-resolution mass spectrometry approach and western blot validation, we found that two fragments of the myofibrillar structural protein myomesin-3 (MYOM3) are abnormally present in sera of Duchenne muscular dystrophy (DMD) patients, limb-girdle muscular dystrophy type 2D (LGMD2D) and their respective animal models. Levels of MYOM3 fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 71 publications
(87 reference statements)
7
79
2
Order By: Relevance
“…ELISA) are perhaps preferable. Along this line, Rouillon et al 28. found that two fragments of the myofibrillar structural protein myomesin-3 (MYOM3) were abnormally present in sera of DMD patients, limb-girdle muscular dystrophy type 2D (LGMD2D) and animal models of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…ELISA) are perhaps preferable. Along this line, Rouillon et al 28. found that two fragments of the myofibrillar structural protein myomesin-3 (MYOM3) were abnormally present in sera of DMD patients, limb-girdle muscular dystrophy type 2D (LGMD2D) and animal models of these diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of biomarkers for DMD is a priority to the field to identify prognostic factors and to provide objective readouts to reliably evaluate patients' response to drugs in clinical trials . Several muscle specific molecular entities have been detected in biofluids such as serum, plasma, and urine showing that it is possible to obtain direct muscle‐related information without an invasive muscle biopsy . Muscle‐derived proteins such as muscle creatine kinase (CK) are known to be highly elevated in patients' blood in the early phases of the disease and to decrease over time as muscle mass is lost .…”
Section: Introductionmentioning
confidence: 99%
“…However, mCK demonstrates variations due to physical activity, muscle injury, cramping, toxic agents or age19, and thus is of limited utility for disease assessment. Other dysregulated serum proteins in DMD disease, the muscle metalloproteinase-9 (MMP-9)20 and myomesin-321, are under investigation as candidate biomarkers. Another class of circulating molecules that can potentially be used as monitoring biomarkers is the microRNAs (miRNAs).…”
mentioning
confidence: 99%